Recent Advances in Pen‐Based Writing Electronics and their Emerging Applications. (January 2016) - Li, Zedong; Liu, Hao; Ouyang, Cheng; Hong Wee, Wei; Cui, Xingye; Jian Lu, Tian; Pingguan‐Murphy, Belinda; Li, Fei; Xu, Feng
Abstract : The emerging demand for cost‐effective, easily accessible, and rapid prototyping electronics fabrication calls for novel techniques to design and manufacture electronic components and devices for wearable functional sensing, on‐skin medical monitoring, and body‐worn energy conversion. Inspired by daily hand‐writing, innovative and ubiquitously available pens can be employed to write conductive patterns on multiple substrates; such a low‐cost, fast, and user‐friendly direct writing paradigm has recently aroused remarkable research interest as a promising electronics prototyping strategy. In this review, state‐of‐art advances in techniques for direct writing of electronics are presented, and pros and cons of each fabrication route are discussed. Emerging applications of pen‐based writing electronics are also summarized. Based on these, final conclusions, limitations and challenges, as well as ongoing perspectives are illustrated. Abstract : Inspired by daily hand‐writing, ubiquitously available pens have recently been employed to directly write electronics. Increasing demand for cost‐effective and easily accessible fabrication of electronics that also allows for rapid prototyping calls for novel techniques to design and manufacture electronics. State‐of‐art advances in pen‐based writing electronics and emerging applications are summarized.